(untitled) (UNWE Yearbook, 2009)
On the look-out for increased competitiveness new forms of employment, which differ from the standard form of labour, are used by businesses. The flexible forms of employment (FFE) fit the state-of-the-art strategies of increased employment, higher efficiency and the quality of labour. These should also be regarded as key strategies for the development of small-and medium-size enterprises (SME), which in Bulgaria represent the overwhelming share of all enterprises and cover half of the workers and employees in the country.The study highlights the basic results of the 2007 survey of the application of FFE in SME. The subject matter of the study are the conditions and opportunities for the development of internal flexibility, i.e. the spread of the different forms of employment in SME. The paper features an assessment of employees’ and employers’ attitudes, as well the openings for a wider use of FFE in human resource management, employment conditions and social security.The study outlines the advantages and the drawbacks in the use of FFE. Proposals are submitted aimed at enhancing the efficiency of MSE, more specifically, in terms of human resource management.